Instability and decline of participatory budgeting in Brazilian and Portuguese municipalities (2016-2019) - Lüchmann, Lígia Helena Hahn; Bogo, Rodrigo Sartori [UNESP] (FapUNIFESP (SciELO), 2022)
To analyze the phenomenon of shrinking municipal participatory budgets (PBs) in Brazil and Portugal, the article presents unprecedented data on the occurrence of these participatory processes comparing the years of 2016 and 2019. The results find that, despite a decrease in cases in both countries, Brazil shows a drop of more than 80% in PB cases in this period, while the index in Portugal is of almost 22%. Mobilizing the theoretical field of public policies, the article discusses the importance of political-partisan electoral changes and suggests that the abandonment of PBs not only occurs due to the change of governments, among other elements, but also correlates to the effects of creation and growth of other less demanding formats of participation, such as public hearings in Brazil and sectorial modalities of PBs, in addition to digital modalities in Portugal.
Inestabilidad y disminución del Presupuesto Participativo en municipalidades de Brasil y Portugal (2016-2019)
Instabilité et déclin des budgets participatifs dans les municipalités du Brésil et du Portugal (2016-2019)
Keywords: Brazil; decline; participation; participatory budgeting; Portugal